Exploration of simulated urine sample biochemistry for the diagnosis of diseases: A laboratory practical exercise. Issue 5 (21st May 2021) - Denis, Colette; Lasfargues, Charline; Buffin‐Meyer, Bénédicte
Abstract: The practical work described here is designed for third‐year bachelor students in Life Sciences attending a kidney physiology course. It illustrates how urinary biochemistry can be used for a medical diagnosis. Students have to measure glucose, proteins, and creatinine concentrations in three simulated urine samples. First, they independently elaborate detailed protocols from the biochemical kit's technical sheets. Second, after correction of the protocols by the teacher, they perform the biochemical assays. Finally, students write a report in which they interpret the biochemical data and use them in the context of histological images assigned to each urine sample. With their results, their theoretical background and scientific articles supplied by the teacher, they establish the diagnosis indicating which patients are diseased and from which disease they are suffering (diabetes without nephropathy, diabetic nephropathy or hypertensive nephropathy). The originality of this practical work is to give student autonomy from the start of the project by requiring them to write the protocols, and determine the diagnosis by themselves. Simple and inexpensive, this practical forces students to mobilize their knowledge in renal physiology and pathophysiology as well as those acquired in other disciplines such as biochemistry or cellular biology. A survey conducted on two classes of students confirmed that this type of training helps students to better understand renal physiology, to realize the importance of interdisciplinarity (biochemistry, histology, and physiology) and to develop confidence in their ability to work independently.